Gross Domestic Product Energy Intensity Level as a Criterion for Evaluating the Energy Security of National Economy - Pysar, Nadiia; Viktoria, Dergachova; Vynogradova, Olena; Guseva, Olga (International Journal of Energy Economics and Policy, 2020)
The study deals with the dynamics of the actual Ukrainian gross domestic product (GDP), the level of its energy intensity as a criterion of evaluating the energy security of the national economy. The level of consuming fuel and energy resources in Ukraine for the last seven years was evaluated. The author built a correlation model of dependency of the actual Ukrainian GDP on total fuel consumption volume by Ukrainian industry, industrial production volume, degree of wear of fixed production assets, number of enterprises using advanced production technologies. National economic losses due to non-efficient use of fuel and energy resources were calculated on the basis of the correlation model. The pace of GDP increase was also calculated. The model of functional dependency of national economy energy efficiency on the level of actual Ukrainian GDP energy intensity and transfer from separate values to determinants was made by index method. Keywords: GDP, correlation model, energy intensity, energy efficiency, economic losses, fuel and energy resources, strategy. JEL Classifications: B41. R13. O11. E60 DOI: https://doi.org/10.32479/ijeep.9420